Penggunaan Ayat Al-Quran dalam Produk Pakaian Muslimah: Analisis Semiotika Charles Sanders Peirce pada Akun Instagram @Biabyzaskiamecca - Salehudin Pole (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2022)
The change to the digital era is an extraordinary evolution of human civilization, which involves technological resources. This can be proven by the ease with which anyone can access anything through digital media. At the same time, it gave birth to various activities. One of them is the emergence of a variety of selling Muslim clothing products with modern and classic concepts which later became a market field. From 1980-1990, syar'i clothing was discriminated against. The change in the political system in 1998 had an impact on freedom of dress, especially expressing religious symbols in the use of the hijab. Muslim clothing products are also growing rapidly and become the lifestyle of the Indonesian Muslim middle-class community. In popular culture, the hijab is not merely a cover for their genitals, but also a commodity and "fashion" for them. This in the end eliminates the value of spirituality, as well as presents a new meaning of piety in religious symbols.